Penyuluhan Sistem Informasi Dalam Peningkatan Mutu Layanan Akademik Sekolah Dasar - Enjang Yusup Ali; Ali Sudin; Dede Tatang Sunarya; Cucun Sunaengsih (Universitas Pendidikan Indonesia, 2022)
The purpose of the activity is to provide training to all stakeholders in elementary schools from principals, teachers, administrative managers and students in recognizing and utilizing Information and Communication Technologies (ICT) facilities. Information technology is the means and infrastructure of systems (hardware, software, brainware) and methods for obtaining, transmitting, processing, interpreting, storing, organizing and using data meaningfully. This training transforms knowledge and skills in the operationalization of academic service information system management. This community service activity was carried out in Sumedang Regency at the Elementary School level. Several stages of activities will be carried out to ensure that academic services in schools are able to answer the needs of the community as a form of implementing quality values.